2010
DOI: 10.1111/j.1472-8206.2010.00899.x
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin modulates circulatory lipid peroxidation, anti-oxidant status and hepatic alcohol metabolizing enzymes in rats with ethanol induced liver injury

Abstract: We have investigated the modulatory efficacy of naringenin on circulatory lipid peroxidation and anti-oxidant status, hepatic alcohol metabolizing enzymes in rats with ethanol induced hepatotoxicity. Rats were divided into four groups: groups 1 and 2 received isocaloric glucose and 0.5% carboxymethyl cellulose; groups 3 and 4 received 20% ethanol equivalent to 6 g/kg body weight everyday for the total experimental period of 60 days. In addition, groups 2 and 4 were given naringenin (50 mg/kg) everyday for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 44 publications
(39 reference statements)
2
27
0
Order By: Relevance
“…NAR was able to prevent LPO due to its molecular structure; perhaps its hydroxyl groups facilitate its adherence to lipid bilayer polar groups, and its nonpolar nucleus may interact with hydrophobic tails of phospholipids, thereby reducing the deleterious effects of free radicals on membranes[12,42,43]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NAR was able to prevent LPO due to its molecular structure; perhaps its hydroxyl groups facilitate its adherence to lipid bilayer polar groups, and its nonpolar nucleus may interact with hydrophobic tails of phospholipids, thereby reducing the deleterious effects of free radicals on membranes[12,42,43]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition to its antioxidant properties as a free radical scavenger, NAR may also act though Nrf2 activation and induce endogenous antioxidant enzymes. In fact, NAR upregulates the expression of the enzyme glutamate-cysteine ligase, the rate limiting enzyme involved in de novo GSH synthesis[44-48], as well as glutathione reductase, which catalyzes the reduction of oxidized glutathione to the reduced form[15,43]. GPx detoxifies H 2 O 2 by reducing it to water and oxygen, utilizing two molecules of GSH to form GSSG in the reduction of a molecule of H 2 O 2 [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found abundantly in Citrus species. Naringenin and hesperidin are flavonoids that present highly in C. hystrix [14] , concentrated in peels [15] . Powerful antioxidant and free radicals scavenging activity of these compounds have been noted [10,18] .…”
Section: Discussionmentioning
confidence: 99%
“…A study reported that among parts of the plant, highest yield of extraction was obtained from peels [14] . Antioxidant activity and free radicals scavenging properties of naringenin and hesperidin have been examined by numerous researchers using various assay systems [15,16] . Naringenin could increase CD 4+ / CD 8+ ratio on T cell which is responsible for immune system [17] , while hesperidin could enhance innate and adaptive immune system [18] , and cardioprotective effect on doxorubicin induced rats [19] .…”
Section: Introductionmentioning
confidence: 99%